Pengembangan Media Pembelajaran Alignment pada Pulley dan Kopling Menggunakan Metode Cahaya Laser dan Dial Indicator pada Mata Kuliah Praktik Alignment - Aminuddin Aminuddin; Muhammad Nur (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
The purpose of this study was to develop alignment learning media on pulleys and couplings using laser light methods and dial indicators in alignment practice courses. This research method used research and development (R&D). The subjects of this study were 16 third semester students. The instruments used were questionnaires and tests. The data analysis technique used in this research was statistical analysis with t-test. The results of this study indicate that the media expert's validity test scores 4 and this shows that the learning media is made attractive and effective in its use, the results of the pre-test and post-test scores, namely that there is an increase in student scores from an average value of 48.5 to 79.6. or if in percentage there is an increase of 63.9% of all student grades. The test results using SPSS where the mean value of the post test was 79.69> of the pre test was 48.75, while in the paired sample correlations the value was Sign. 0.000 <than 0.05, it can be said that there is a relationship between the Pre Test variable with the Post Test and Paired Samples Test variables of 0.000 <0.05.